Perspectives for agglomerations in Western Germany - Lorenz, Cornelia (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
The development pressure on agglomerations in the western part of Germany will continue into the future. It was in order to counter the negative trends associated with this situation that the spatial order principles of settlement density, mixed uses and polycentrality were developed. However, these strategies can only be implemented through a tier of administration which covers the expanding conurbation in its entirety. Consequently, this calls for a reorganisation of the regional planning system in which strategies are developed in close co-operation with local authorities to overcome these problems and to equip it with the instruments it requires to implement these strategies.